Bcr-abl peptides for chronic myeloid leukemia (Hematology Meeting Reports, 2009)
In these recent years, treatment of CML has been notably improved by imatinib mesylate a potent tyrosine kinase inhibitor that blocks the kinase activity of p210, thus inhibiting the proliferation of Ph-positive progenitors.1 In chronic phase patients treated with Imatinib mesylate, the kinetic of response, particularly cytogenetic response, is most of the time rapid, with a major and even complete cytogenetic remission (CCR) observed within 6-12 months of therapy.2,3 However, molecular remissions are rare4 and up-front resistance to Imatinib as well as loss of response during treatment is of increased concern.5,6 For all these reasons, despite the fact that Imatinib represents the current most effective de-bulking therapy for chronic phase CML and the actual best conventional treatment for CML patients, the eradication of residual disease and possibly the cure without bone marrow transplantation still appears a difficult goal for a tyrosine kinase inhibitor approach alone in these patients.7